DAMPAK ALIH FUNGSI LAHAN TERHADAP KEBERLANJUTAN SUPLAI AIR DI WADUK SUTAMI, MALANG, JAWA TIMUR - M. Luthful Hakim (Pusbindiklat - LIPI, 2010)
The research about impact of landuse change from forest become the non-forest in watershed of Upstream Brantas on decreasing water supply in Sutami Dam have been done. The objective of this research were: 1) to study impact of landuse change from forest become the non-forest (shrubs, farm/garden, or urban) on water supply sustainability in Sutami Dam, and 2) to determine an optimal landuse of forest on water supply sustainability. The location of research site is on watershed of Upstream Brantas, Malang, East Jawa. The methods of data analysis were: 1) analysis of landuse type, 2) analysis of hydrology, 3) model accuration testing, and 4) optimation of landusearea and position on decreasing runoff discharge and increasing baseflow discharge. The result showed landuse change from forest become the non-forest during 6 year (1997-2003) a significant impact on water production decrease in Sutami Dam (increasing runoff discharge 79% and decreasing baseflow discharge 90% compared to year 2001. The optimal landuse of forest area to sustainability of water supply was 43%.